Tax Payment Trends in Lithuania in 2008–2009 - Anciūtė, Aurelija (Lithuanian Journal of Statistics, 2010)
The article discusses the most important changes in the Lithuanian tax system, which took effect on 1 January 2009. The main focus is on tax payment trends, i.e. what are the patterns of tax revenue stream determined by the legal basis, how the revenue stream is influenced by legislative changes, what is the relationship between the country’s economic situation and the main sources of national budget revenue (value added, individual and company income taxes, excise duties).Changes in the tax system can be divided into several categories: changes in tax rates, abolition of tax exemptions, changes in tax calculation, declaration and payment procedures. All of these changes were a challenge to both taxpayers and tax administrators due to an extremely short period between amendments to legislation and the actual moment when they came into force. It should be noted, however, that, although the changes in the tax system provided additional income to the national budget, the contracting economy forced the national government to reduce the expectations related to the tax revenue stream.The article also contains a few alternative views on the growth in the black economy, which is often said to be one of the consequences of tax system changes. Moreover, the so-called “Phoenix” syndrome is discussed.
Keywords: none